Dynamic landslide processes revealed by broadband seismic records. Issue 12 (20th June 2013) - Yamada, Masumi; Kumagai, Hiroyuki; Matsushi, Yuki; Matsuzawa, Takanori
<x xml:space="preserve">Abstract</x> [1] We use broadband seismic recordings to trace the dynamic process of the deep‐seated Akatani landslide that occurred on the Kii Peninsula, Japan, which is one of the best recorded large slope failures. Combining analyses of the seismic records with precise topographic surveys done before and after the event, we can resolve a detailed time history of the mass movement. During 50 s of the large landslide, we observe a smooth initiation, acceleration with changes in basal friction, and reversal of the momentum when the mass collides with the opposite valley wall. Of particular importance is the determination of the dynamic friction during the landslide. The coefficient of friction is estimated to be 0.56 at the beginning of the event and drops to 0.38 for most of the sliding. The change in the frictional level on the sliding surface may be due to liquefaction or breaking of rough patches and contributes to the extended propagation of the large landslide.